SAW Method in Decision Making for Scholarship Recipients Faculty of Computer Science Indonesian Christian University Maluku - Leipary, Harfely; Tuhuteru, Hennie; Patty, Joanna C (Jurnal Multidisiplin Madani, 2024)
The process of selecting scholarship recipients in academic institutions necessitates a meticulous and unbiased approach to ensure the fair distribution of educational resources. This study employs the Simple Additive Weighting (SAW) method to enhance decision-making in the Faculty of Computer Science at the Indonesian Christian University, Maluku. The SAW method provides a structured framework for evaluating scholarship candidates based on multiple criteria, including academic performance, extracurricular activities, and financial need. Through criteria normalization, weight assignment, and score calculation, the SAW method facilitates an objective ranking of candidates, allowing for a transparent and systematic decision-making process. The research aims to improve the efficiency and fairness of scholarship allocation, contributing to the advancement of educational opportunities for deserving individuals within the Faculty of Computer Science